2022
DOI: 10.1021/acsami.2c15187
|View full text |Cite
|
Sign up to set email alerts
|

Steroid-Aromatics Clathrates as Chiroptical Materials with Circularly Polarized Luminescence and Phosphorescence

Abstract: Solid-state host−guest complexation shows great potential in the fabrication of chiroptical and phosphorescent materials. Developing chiral hosts toward achiral guests with a wide guest scope would expand the chiroptical application, which however remains a major challenge. Here, we report the steroidaromatic compound complexation in the solid state that could realize effective chirality transfer, circularly polarized luminescence, and room temperature phosphorescence (RTP). Progesterone shows cocrystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Bromo-naphthalimide compounds displayed long-lived phosphorescence when doped in molecular hosts. The formation of clathrate-like structures in the host–guest complexation offers a rigid environment to lower the nonirradiative transitions, and thus, the triplet excitation states would be stabilized to give phosphorescence. L G1 was doped into different hosts using the melting/cooling protocol thanks to the relatively low melting points of hosts. Among the four employed hosts, H1 exclusively induced the emergence of bathochromic-shifted red emission.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bromo-naphthalimide compounds displayed long-lived phosphorescence when doped in molecular hosts. The formation of clathrate-like structures in the host–guest complexation offers a rigid environment to lower the nonirradiative transitions, and thus, the triplet excitation states would be stabilized to give phosphorescence. L G1 was doped into different hosts using the melting/cooling protocol thanks to the relatively low melting points of hosts. Among the four employed hosts, H1 exclusively induced the emergence of bathochromic-shifted red emission.…”
Section: Resultsmentioning
confidence: 99%
“…Selectively, L G1 induced P -handedness for H1 to H3 and M -handedness for H4, where the chiral recognition is entropy dependent based on the density functional (DFT) theory-based computations. Specifically, G1/H1 constitutes into a host–guest pair that allows for room-temperature phosphorescence (RTP) by providing a rigid environment to enable triplet transitions. A minimal amount of G1 triggers RTP and homochirality in a synergistical way, which generates a red circularly polarized phosphorescence (CPP). Importantly, the emergence of CPP and circular dichroism is well controlled by heating–cooling treatment whereby a thermal chiroptical switch is successfully realized (Scheme b). This work illustrates an efficient chiral recognition and amplification protocol to design phosphorescent thermal chiroptical switchable materials, which surely inspires the future exploration of conglomerate crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Selective absorption from CDs emission produced by PSA film leads to circularly polarized signals. Xing et al indicated that CP-RTP could be induced by chiral transfer between host and guest (Scheme 4f) 38 . Progesterone (Pg) shows cocrystallization behaviour toward a wide range of guests through CH-π interactions, offering a rigid and chiral microenvironment to entrap aromatic luminophores within the cavities.…”
Section: Cp-rtp Systems Based On Planar Chirality and Othersmentioning
confidence: 99%
“…Xing et al indicated that CP-RTP could be induced by chiral transfer between host and guest (Scheme 4f ). 38 Progesterone (Pg) shows cocrystallization behaviour toward a wide range of guests through CH-π interactions, offering a rigid and chiral microenvironment to entrap aromatic luminophores within the cavities. The handedness of the Cotton effects and CPL could be tuned.…”
Section: Purely Organic Cp-rtp Materialsmentioning
confidence: 99%
“…The most distinctive manifestation of chirality in chemistry is the optical activity of chiral structures, expressed as optical rotation or circular dichroism (CD). Chiral materials have demonstrated broad application prospects, such as in asymmetric catalysis, chiral sensing, chiral separation, and so on. On the other hand, chirality can be divided into configurational chirality, conformational chirality, and phase chirality at molecular scales . As far as chiral polymers are concerned, the relevant research has mainly focused on conformation chirality and phase chirality.…”
Section: Introductionmentioning
confidence: 99%